Zgodnjesrednjeveška naselbina na blejski Pristavi = Frühmittelalterliche Siedlung Pristava in Bled Tafonomija, predmeti in čas = Taphonomie, Fundgegenstände und zeitliche Einordnung - Pleterski, Andrej (Opera Instituti Archaeologici Sloveniae, 2010)
Pristava in Bled belongs among those archaeological sites which, in the extent and inter-connectedness of the information they provide, represent a pattern in which numerous general processes are revealed. In solving the puzzle of Pristava, we are also to a great extent settling altogether the generally unresolved problems of the Eastern Alps in the Early Middle Ages.Firstly, a taphonomic analysis of the settlement is presented. This is followed by a classification of the earthenware and its absolute dating. In order to do this, a completely new dating procedure was developed. Although by no means simple, it has nevertheless proved to be both applicable and successful. It is now generally available and of assistance to all.